A Single Session of tDCS Stimulation Can Modulate an EEG Microstate Associated With Anxiety in Patients With Depression - Keiichiro Nishida; Shota Minami; Tomonari Yamane; Satsuki Ueda; Banri Tsukuda; Shunichiro Ikeda; Daisuke Haruna; Masafumi Yoshimura; Tetsufumi Kanazawa; Thomas Koenig (Brain and Behavior)
ABSTRACT Purpose Microstate analysis involves examining the temporal dynamics of electroencephalogram (EEG) signals and serves as a crucial method for exploring the neural basis of psychiatric disorders. This study investigates the effects of transcranial direct current stimulation (tDCS) on specific microstate parameter maps‐D and C in patients with depression, specifically targeting the dorsomedial prefrontal cortex (DMPFC) and left dorsolateral prefrontal cortex (DLPFC). Methods We conducted an open‐label, between‐subject, crossover trial involving 19 patients clinically diagnosed with depression. A 1 mA electrical current was administered, with anodal stimulation specifically targeting the DMPFC or the left DLPFC. Microstate maps were derived from resting‐state EEG recordings obtained prior to and following the application of tDCS. The EEG data were categorized into five distinct microstate classes for subsequent analysis. Findings The findings revealed a significant increase in the duration of microstate class D following stimulation in both groups, while microstate class C exhibited no notable changes. Additionally, a significant association was identified between the transition from microstate D to C and alterations in the State‐Trait Anxiety Inventory‐State (STAI‐S) scores after left DLPFC stimulation. Conclusion Microstate map D appears to be associated with psychiatric disorders and executive functions, whereas map C may relate to the salience network and mind‐wandering. Our findings suggest that microstate maps D and C are responsive to tDCS stimuli, indicating their potential as objective tools for anxiety assessment. Employing transition‐focused parameters in EEG microstate analysis may enhance the tracking of rapidly fluctuating emotional states, rather than relying solely on duration metrics. Furthermore, the integration of non‐invasive brain stimulation techniques, such as tDCS, with EEG microstate analysis holds significant promise for elucidating the neural mechanisms involved in depression. Trial Registration UMIN‐CTR Clinical Trial: UMIN000015046